PEMINJAMAN DAN PENYERAPAN KOSAKATA KULINER DALAM BAHASA INDONESIA: REPRESENTASI BUDAYA MILENIAL DAN Z - Yermia Nugroho Agung Wibowo; Syamsul Sodiq; Heny Subandiyah; Mixghan Norman Antono (Jurnal Online Baradha, 2026)
Culinary vocabulary continues to develop along with the development of culinary arts in Indonesia. This vocabulary is used by the public and has become a popular vocabulary, especially vocabulary related to food, along with the interest of millennials and Z generations in culinary that is "contemporary". Unfortunately, the development of culinary vocabulary is not comparable to the culinary vocabulary in the Kamus Besar Bahasa Indonesia (KBBI). Therefore, this study aims to describe the borrowing and absorption of culinary vocabulary in Indonesian that represents millennial and Z culture. Research data collection was carried out using reading-noting and listening-noting techniques. The research data is culinary vocabulary used by the Indonesian people. Data sources are online KBBI, culinary magazines, and culinary videos on YouTube. Data analysis used intralingual and extralingual matching techniques. The results of the study consist of (1) there is borrowing of culinary vocabulary in the fields of meaning of food ingredients, tools, food processing, texture and taste, food names; (2) absorption of culinary vocabulary is carried out by adopting and adapting writing; (4) variations in culinary vocabulary are found in the form of combinations with other words; (5) borrowing and absorption of culinary vocabulary are dominated by food names from Japanese and Korean vocabulary which also represent millennial and Z culture. Keywords: vocabulary borrowing, vocabulary absorption, culinary, millennial and Z culture Abstrak Kosakata kuliner terus berkembang seiring dengan perkembangan kuliner di Indonesia. Kosakata tersebut digunakan masyarakat dan menjadi kosakata populer, terutama kosakata yang berkaitan dengan makanan, seiring dengan minat generasi milenial dan Z terhadap kuliner yang bersifat “kekinian”. Sayangnya, perkembangan kosakata kuliner tersebut tidak sebanding dengan kosakata kuliner di Kamus Besar Bahasa Indonesia (KBBI). Sebab itu, penelitian ini bertujuan untuk mendeskripsikan peminjaman dan penyerapan kosakata kuliner dalam bahasa Indonesia yang merepresentasikan budaya milenial dan Z. Pengumpulan data penelitian dilakukan dengan teknik baca-catat dan simak catat. Data penelitian adalah kosakata kuliner yang digunakan oleh masyarakat Indonesia. Sumber data adalah KBBI daring, majalah kuliner, dan video kuliner di youtube. Analisis data menggunakan teknik padan intralingual dan ekstralingual. Hasil penelitian terdiri atas (1) terdapat peminjaman kosakata kuliner pada medan makna bahan makanan, alat, pengolahan makanan, tekstur dan rasa, nama makanan; (2) penyerapan kosakata kuliner dilakukan dengan cara adopsi dan adaptasi penulisan; (4) ditemukan variasi kosakata kuliner berupa penggabungan dengan kata lain; (5) peminjaman dan penyerapan kosakata kuliner didominasi oleh nama makanan dari kosakata Jepang dan Korea yang sekaligus merepresentasikan budaya milenial dan Z. Kata kunci: Peminjaman kosakata, penyerapan kosakata, kuliner, budaya milenial dan Z